2015
DOI: 10.1542/peds.2014-0793
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-Assessment of Pubertal Maturation

Abstract: BACKGROUND AND OBJECTIVES: Studies of adolescents often use self-assessment of pubertal maturation, the reliability of which has shown conflicting results. We aimed to examine the reliability of child and parent assessments of healthy boys and girls.METHODS: A total of 898 children (418 girls, 480 boys, age 7.4-14.9 years) and 1173 parents (550 daughters, 623 sons, age 5.6-14.7 years) assessed onset of puberty or development of breasts, genitals, and pubic hair according to Tanner stages by use of a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(178 citation statements)
references
References 30 publications
3
165
2
8
Order By: Relevance
“…These κ values were slightly higher than those reported in other studies, where estimates have ranged from 0.67 to 0.90, indicating substantial agreement, 20,21,32,33,39 with some exceptions. 40 We found that almost three-quarters of mothers accurately assessed breast Tanner stage compared with the clinical assessment.…”
Section: Accuracy Of Breast Development Versus Clinical Assessment Ascontrasting
confidence: 71%
See 3 more Smart Citations
“…These κ values were slightly higher than those reported in other studies, where estimates have ranged from 0.67 to 0.90, indicating substantial agreement, 20,21,32,33,39 with some exceptions. 40 We found that almost three-quarters of mothers accurately assessed breast Tanner stage compared with the clinical assessment.…”
Section: Accuracy Of Breast Development Versus Clinical Assessment Ascontrasting
confidence: 71%
“…40,43,[45][46][47] Previous studies have shown a wide range of accuracy for self-assessed pubic hair staging, 40,45,47,48 although 2 studies that also examined mother report suggest that self-staging may be more reliable than maternal staging for pubic hair development. 33,41 We found that girls were more likely to report a higher stage of pubic hair development than their mothers.…”
Section: Maternal Versus Self-staging Of Pubic Hair Developmentmentioning
confidence: 73%
See 2 more Smart Citations
“…However, the reliability self-assessment of pubertal maturation has shown conflicting results. According to Ramussen et al 1 the pubertal assessment by the child or the parents is not a reliable measure of exact pubertal staging and should be augmented by a physical examination.…”
Section: Articles Identified N = 324mentioning
confidence: 99%